Peran Organisasi Masyarakat Sipil dalam Pemberantasan Hoaks - Muhammad Edy Susilo; Subhan Afifi; Senja Yustitia (Eksos LPPM, 2020)
Hoax or fake news in Indonesia are increasing along with the use of social media. Towards the 2019 general elections, the intensity of political hoaks is increasingly widespread. Hoax can target anyone, but are intended specifically for competing candidates. Hoax have the potential to cause conflict in society and break up national unity. The government has done many things to eradicate hoaks. However, eradication involve many stakeholders, one of them is civil society organizations. The Research question is how the role of civil society organizations in Indonesia in eradicating hoaks. The study was conducted with qualitative methods. Data obtained from various civil society organizations that relevant to the topics. The results showed that all organizations that studied, they all support to eradicate hoaks. Hoaks are counterproductive in the life of the nation and state. All organizations have also done many things in accordance with their fields. However, they also have limitations. Government is the most responsible for hoax eradication. In this study, there is one finding interesting about Islamic organizations that feel unfairly treated in hoax eradication. This should be a concern for the government if they are really serious about eradicating hoaxes. Keywords: hoax, civil society organization, election, conflict.